2017
DOI: 10.3389/fnbeh.2017.00083
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Orexin-2 Receptors Prevents Stress-Induced ACTH Release in Mice

Abstract: Orexins peptides exert a prominent role in arousal-related processes including stress responding, by activating orexin-1 (OX1R) and orexin-2 (OX2R) receptors located widely throughout the brain. Stress or orexin administration stimulates hyperarousal, adrenocorticotropic hormone (ACTH) and corticosterone release, and selective OX1R blockade can attenuate several stress-induced behavioral and cardiovascular responses but not the hypothalamic-pituitary-adrenal (HPA) axis activation. As opposed to OX1R, OX2R are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Lateral hypothalamic orexinergic neurons have previously been demonstrated to be involved in maintaining wakefulness 18 and show high neuronal activity during wake state while they are virtually silent during sleep 19,20 . OX activates both OX1R and OX2R during stress 21 , resulting in HPA activation which can be prevented selectively by OX2R antagonists 22 and increased blood pressure and heart rate 23,24 , which can be prevented by OX1R antagonists 25 . In rodents OX antagonists ameliorated behavioral consequences of chronic unpredictable stress, normalized HPA axis function 26 , and attenuated an OX-induced increase in adrenocorticotropic hormone levels 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Lateral hypothalamic orexinergic neurons have previously been demonstrated to be involved in maintaining wakefulness 18 and show high neuronal activity during wake state while they are virtually silent during sleep 19,20 . OX activates both OX1R and OX2R during stress 21 , resulting in HPA activation which can be prevented selectively by OX2R antagonists 22 and increased blood pressure and heart rate 23,24 , which can be prevented by OX1R antagonists 25 . In rodents OX antagonists ameliorated behavioral consequences of chronic unpredictable stress, normalized HPA axis function 26 , and attenuated an OX-induced increase in adrenocorticotropic hormone levels 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Seltorexant blocks OX2Rs which are present in the paraventricular nucleus of the hypothalamus (Yun et al, 2017). As a result, HPA-axis function and therefore hyperarousal can theoretically be attenuated.…”
Section: Resultsmentioning
confidence: 99%
“…Yun and colleagues recently demonstrated that the involvement of the orexin system in stress response is even more profound. A typical hormonal reaction to stress—an increase in serum levels of adrenocorticotropic hormone (ACTH)—was absent in stress-exposed mice pretreated with selective OX2R antagonist [ 55 ].…”
Section: Hidden Pacemaker—the Influence Of Orexins On the Autonomic Smentioning
confidence: 99%